Learning to Surrender: Creative teaching and learning practices - Ihnatovych, Diana (McGill Journal of Education / Revue des sciences de l'éducation de McGill, 2020)
Independence and critical thinking are crucial for survival in our contemporary world. Learners and new teachers in training should be trusted to discover and develop their own voice in teaching and learning and be encouraged to surrender expectation to produce predetermined outcomes by strictly following scripted curriculum because it is detrimental to learners and teachers alike as it does not foster independence and critical thinking. Through engaging in creative teaching and learning practices that encourage imagination, questioning, observation and reflection we can see beyond what is perceived as normal and understandable and seek new ways to interpret reality and experience things of everyday life as well as learn to listen to our students and support them in their own discovery.